4p-4=p+4

Simple and best practice solution for 4p-4=p+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p-4=p+4 equation:


Simplifying
4p + -4 = p + 4

Reorder the terms:
-4 + 4p = p + 4

Reorder the terms:
-4 + 4p = 4 + p

Solving
-4 + 4p = 4 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-4 + 4p + -1p = 4 + p + -1p

Combine like terms: 4p + -1p = 3p
-4 + 3p = 4 + p + -1p

Combine like terms: p + -1p = 0
-4 + 3p = 4 + 0
-4 + 3p = 4

Add '4' to each side of the equation.
-4 + 4 + 3p = 4 + 4

Combine like terms: -4 + 4 = 0
0 + 3p = 4 + 4
3p = 4 + 4

Combine like terms: 4 + 4 = 8
3p = 8

Divide each side by '3'.
p = 2.666666667

Simplifying
p = 2.666666667

See similar equations:

| 2(3+5x)=86 | | 4p-4=p | | 10a-14=286 | | (3y-5)+(5y+20)=-22 | | y-15=2(x-6) | | 89+3=21 | | X+8+2x-1=11 | | 18=8(u-3)-2u | | (5m-10)(m+4)=0 | | -6=2x+2(x+3) | | c(200)=6.2x+10100 | | 15+12/2= | | X+8=76 | | -10n+4=-86 | | (5+7i)(4-12i)= | | -11x+12=-7x | | 86900=-19.2+2.4x | | y+7=8(x-1) | | 9+3x+12=8x-9-5x | | 7y+6(y-4)=2 | | c(200)=6.2+10100 | | 3x-2(8-2x)=5 | | 2x=2+-14 | | X-0.75=1.00 | | 6=2(y-7)-7y | | 3-5k=88 | | 6+-x=1 | | h-25=2h-8 | | m-1=96 | | 8(-8x-6)=6x-22 | | 2n+n-6=30 | | -4=(v+1) |

Equations solver categories